Quadruple Helix Collaboration Concept As An Economic Recovery Solution After Covid-19 (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2022)
The COVID-19 pandemic has had a severe impact on the health, economic, transportation, and other industrial crises. The implementation of the lockdown or PSBB has affected the operations of various economic sectors. The purpose of this research is to describe the concept of Quadruple Helix collaboration as part of the collaboration and synergy initiative between multi actors to help find solutions as an effort to recover the national economy after COVID-19 in implementing government policies. The research method used is a descriptive qualitative method using secondary data from various literature sources, such as books, articles, the home page, to access information data relevant to the Quadruple Helix collaboration concept, namely government, academia, company, and society. Research result. The analysis technique was carried out by descriptive analysis. Based on the research results, it can be seen that the Quadruple Helix collaboration concept is a solution for national economic recovery, which can refer to the structure, process, input, and output